A COMPARATIVE STUDY OF JOB ENRICHMENT BETWEEN MALE AND FEMALE IN DINAS PEKERJAAN UMUM PROVINSI SULUT - Andries, Jazzy .; Lambey, Linda .; Tumiwa, Johan R. (Universitas Sam Ratulangi, 2017)
Abstract: This research is important because through job enrichment, employee can increase job satisfaction by givingemployees the opportunity to use their various abilities. The purpose of this study is to know making the work moreinteresting, challenging and satisfying if comparative studies of Job Enrichment between male and female employees. Thebenefits of this study are to improve employee performance and reduce public complaints about Public Servant. Therecommendation for this research is leaders must be careful when measuring employee performance. Because of that, not allemployees can receive and do job enrichment. This study uses quantitative research and data was collected from the PublicWorks Department of North Sulawesi. The data were analyzed by Independent Sample T-test, to analyze if there anysignificant difference between job enrichment of male and female in Dinas Pekerjaan Umum Provinsi Sulut. The populationof this research is the employees of Dinas Pekerjaan Umum in Sulut, with 50 respondents of male employee and 50respondent of female employee as the sample. The result shows that there is a significant difference between job enrichmentof male and female at Dinas Pekerjaan Umum Sulut.Keywords: job enrichment, male, female